دراسة دلالية لقصيدة مختارة من الشوقيات لعلم والتعليم وواجب المعلم - ذكرى بن يحي (My University, 2023)
Abstract: This study aims to study the semantics of poems from Al-Shawqiyyat, and the theoretical study was based on the study of Ahmed Shawqi’s poem entitled Science, Education, and the Duty of the Teacher, where we touched on the presentation of the semantic fields in this poem from the field of morphological forms, the field of Al-Shawqiyyat, synonyms, verbal cognates, antonyms, implication, and conjunctions, and we extracted them from the previous poem. . The study also concluded several results, the most important of which is that the theory of semantic fields is one of the important turning points in the history of modern semantics. This poem includes several synonyms, antonyms, and morphological forms, so that it is clear to everyone who reads it. ----------------------- الملخص: تهدف هذه الدراسة الى دراسة دلالية لقصائد من الشوقيات، وتم اسقاط الدراسة النظرية على دراسة قصيدة احمد شوقي بعنوان العلم والتعليم وواجب المعلم، حيث تطرقنا الى عرض الحقول الدلالية في هذه القصيدة من حقل صيغ صرفية وحقل الشوقيات ومترادفات والمشترك اللفظي ومتضادات والتضمن والمقترانات واستخرناها من القصيدة السابقة. كما خلصت الدراسة الى عدة نتائج اهمها ان نظرية الحقول الدلالية من النقاط التحولية الهامة في تاريخ لم الدلالة الحديث، وتشمل هذه القصيدة على عدة مترادفات ومتضادات وصيغ صرفية لتكون بذلك واضحة لكل من يقرئها ------------------ Résumé : Cette étude vise à étudier la sémantique des poèmes d’Al-Shawqiyyat, et l’étude théorique a été basée sur l’étude du poème d’Ahmed Shawqi intitulé Science, éducation et le devoir de l’enseignant, où nous avons abordé la présentation des champs sémantiques de ce poème à partir du champ des formes morphologiques, du champ d’Al-Shawqiyyat, des synonymes, des cognates verbaux, des antonymes, des implications et des conjonctions, et nous les avons extraits du poème précédent. L’étude a également conclu plusieurs résultats, dont le plus important est que la théorie des champs sémantiques est l’un des tournants importants de l’histoire de la sémantique moderne. Ce poème comprend plusieurs synonymes, antonymes et formes morphologiques, de sorte qu’il est clair pour tous ceux qui vont le lire..